2018
DOI: 10.1038/s41598-018-34554-w
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced pharmacological efficacy of sumatriptan due to modification of its physicochemical properties by inclusion in selected cyclodextrins

Abstract: The study focused on the pharmacological action of sumatriptan, in particular its antiallodynic and antihyperalgesic properties, as an effect of cyclodextrinic inclusion of sumatriptan, resulting in changes of its physicochemical qualities such as dissolution and permeability through artificial biological membranes, which had previously been examined in vitro in a gastro-intestinal model. The inclusion of sumatriptan into β-cyclodextrin and 2-hydroxylpropylo-β-cyclodextrin by kneading was confirmed with the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…The eligibility of certain kinds of cyclodextrin to achieve the desired stability of the system in solution is determined by the structure of CD and guest API [13]. The thermodynamic effect described by Gibbs free energy of complex formation, as well as by entailed stability constant Ks, can be estimated by structure-based modeling with in silico methods [11,12,[14][15][16][17][18]. Application of theoretical approaches, considering a vast number of testable cyclodextrin derivatives, is an essential tool for streamlining experimental investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The eligibility of certain kinds of cyclodextrin to achieve the desired stability of the system in solution is determined by the structure of CD and guest API [13]. The thermodynamic effect described by Gibbs free energy of complex formation, as well as by entailed stability constant Ks, can be estimated by structure-based modeling with in silico methods [11,12,[14][15][16][17][18]. Application of theoretical approaches, considering a vast number of testable cyclodextrin derivatives, is an essential tool for streamlining experimental investigation.…”
Section: Introductionmentioning
confidence: 99%
“…[50][51][52] In our previous studies, we also confirmed that an increase in the analgesic effect for sumatriptan after introduction into CD structures was possible. 23 Other studies confirming the beneficial impact of CD systems on the analgesic effect were also obtained in the case of ketoprofen, where antipyretic, analgesic and anti-inflammatory effects increased, and in the mice study for meloxicam, where the elevated API serum levels maximized its analgesic activity. 53,54 The strengths of the studies performed include increasing the solubility of TA with a method that can be easily used in the preparation of a drug form for patients.…”
mentioning
confidence: 78%
“…To induce migraine-like pain, nitroglycerin (NTG) (Perlinganit, 1mg/1mL, UCB Pharma GmbH, Germany) was administered by the intraperitoneal route 60 min before further behavioral tests. 23 Behavioral tests were performed at the Department of Pharmacodynamics, Faculty of Pharmacy, Jagiellonian University Medical College in Cracow, Poland. In in vivo tests, 63 adult male Albino Swiss (CD-1) mice weighing between 18 and 22 g were used.…”
Section: Dovepressmentioning
confidence: 99%
See 2 more Smart Citations